2005
DOI: 10.1080/14786410410001709197
|View full text |Cite
|
Sign up to set email alerts
|

A new BIS-Andrographolide Ether from Andrographis paniculata Nees and evaluation of anti-HIV activity

Abstract: Novel bis-andrographolide ether (1) and six known compounds andrographolide, 14-deoxy-11,12-didehydroandrographolide, andrograpanin, 14-deoxyandrographolide, (+/-)-5-hydroxy-7,8-dimethoxyflavanone, and 5-hydroxy-7,8-dimethoxyflavone have been isolated from the aerial parts of Andrographis paniculata and their structures were established by spectral data. All the isolates were tested for the anti-HIV and cytotoxic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…n the process of osteogensis, Wnt5a antagonizes Wnt/ -catenin signaling through the Wnt/Calcium pathway [ ] and -catenin degradation by promoting b [ 4]. tudies ha e shown that haploinsuf iciency of -b can partially rescue dwar ism caused by c P-dependent protein inase de iciency [ 5]. n the -catenin -independent pathway, Wnt5a acti ated Rac by the ac uirement of Frizzled2 (Fzd2) through a clathrinmediated route in response [ ].…”
Section: Discussionmentioning
confidence: 99%
“…n the process of osteogensis, Wnt5a antagonizes Wnt/ -catenin signaling through the Wnt/Calcium pathway [ ] and -catenin degradation by promoting b [ 4]. tudies ha e shown that haploinsuf iciency of -b can partially rescue dwar ism caused by c P-dependent protein inase de iciency [ 5]. n the -catenin -independent pathway, Wnt5a acti ated Rac by the ac uirement of Frizzled2 (Fzd2) through a clathrinmediated route in response [ ].…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide, and 14-deoxy-11,12-didehydroandrographolide have been reported to exhibit anti-HIV activity [34]. Similarly, methanolic extract of M. charantia was found to contain terpenes, saponins and steroids [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…Some of these phytochemicals exhibited a wide range of biological activities such as antiviral , antibacterial , anticancer , antioxidant , and anti‐inflammatory as well as inhibitory activities of the phosphorylation of mitogen‐activated protein kinases . The rich terpenoids and flavones are found to be responsible for the therapeutic effects of leaves of AP . In order to further study the biochemical properties of terpenoids and flavones, and broaden their pharmacological applications, it is necessary to obtain large quantities of highly purified compounds.…”
Section: Introductionmentioning
confidence: 99%